Dark‐field hyperspectral imaging for label free detection of nano‐bio‐materials - Mehta, Nishir; Sahu, Sushant P.; Shaik, Shahensha; Devireddy, Ram; Gartia, Manas Ranjan (Wiley interdisciplinary reviews. Nanomedicine and nanobiotechnology, 2021)
Nanomaterials are playing an increasingly important role in cancer diagnosis and treatment. Nanoparticle (NP)‐based technologies have been utilized for targeted drug delivery during chemotherapies, photodynamic therapy, and immunotherapy. Another active area of research is the toxicity studies of these nanomaterials to understand the cellular uptake and transport of these materials in cells, tissues, and environment. Traditional techniques such as transmission electron microscopy, and mass spectrometry to analyze NP‐based cellular transport or toxicity effect are expensive, require extensive sample preparation, and are low‐throughput. Dark‐field hyperspectral imaging (DF‐HSI), an integration of spectroscopy and microscopy/imaging, provides the ability to investigate cellular transport of these NPs and to quantify the distribution of them within bio‐materials. DF‐HSI also offers versatility in non‐invasively monitoring microorganisms, single cell, and proteins. DF‐HSI is a low‐cost, label‐free technique that is minimally invasive and is a viable choice for obtaining high‐throughput quantitative molecular analyses. Multimodal imaging modalities such as Fourier transform infrared and Raman spectroscopy are also being integrated with HSI systems to enable chemical imaging of the samples. HSI technology is being applied in surgeries to obtain molecular information about the tissues in real‐time. This article provides brief overview of fundamental principles of DF‐HSI and its application for nanomaterials, protein‐detection, single‐cell analysis, microbiology, surgical procedures along with technical challenges and future integrative approach with other imaging and measurement modalities. This article is categorized under: Diagnostic Tools > in vitro Nanoparticle‐Based Sensing Diagnostic Tools > in vivo Nanodiagnostics and Imaging Implantable Materials and Surgical Technologies > Nanoscale Tools and Techniques in Surgery Versatile use of dark‐field hyperspectral imaging for detecting transport of nanomaterials in cells and tissues and for cancer diagnostics.